2012
DOI: 10.2478/v10026-012-0096-z
|View full text |Cite
|
Sign up to set email alerts
|

Bromine catalyst for the methane to methyl bisulfate reaction

Abstract: A catalytic system KBr -oleum is effective at catalyzing the selective oxidation of methane to methanol via. methyl bisulfate. The infl uences of methane pressure, sulfur trioxide and temperature on turnover frequency were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In an effort to extend the reactivity shown with I to Br, Michalkiewicz examined Br – salts in oleum for methane oxidation to MeOSO 3 H. As previous experiments were unsuccessful at lower concentrations of oleum with bromide salts, the authors showed that the reaction proceeds only above 6.6 wt % SO 3 and 500 psi methane.…”
Section: Catalytic Systems That Utilize O2/o2-regenerable Oxidants An...mentioning
confidence: 99%
See 1 more Smart Citation
“…In an effort to extend the reactivity shown with I to Br, Michalkiewicz examined Br – salts in oleum for methane oxidation to MeOSO 3 H. As previous experiments were unsuccessful at lower concentrations of oleum with bromide salts, the authors showed that the reaction proceeds only above 6.6 wt % SO 3 and 500 psi methane.…”
Section: Catalytic Systems That Utilize O2/o2-regenerable Oxidants An...mentioning
confidence: 99%
“…In an effort to extend the reactivity shown with I to Br, Michalkiewicz 151 examined Br − salts in oleum for methane oxidation to MeOSO 3 H. As previous experiments were unsuccessful at lower concentrations of oleum with bromide salts, the authors showed that the reaction proceeds only above 6.6 wt % SO 3 and 500 psi methane. Interestingly, only two systems that have been reported fit into this category, where the stoichiometric oxidant that directly reacts with methane is O 2 -regenerable.…”
Section: Iodinementioning
confidence: 99%
“…Synthesis of methanol 9-11 and formaldehyde 8-13 , oxidative coupling of methane 14 and conversion to aromatics 15 without an oxidant, can be considered as direct conversion ways of methane. The interesting method of methane esterifi cation in the oleum to methyl bisulphate was also studied and described [16][17][18][19][20][21][22] in the literature. The methyl bisulphate can be easily hydrolyzed to methanol 22-28 .…”
Section: Introductionmentioning
confidence: 99%